MITOS ROKAT AENG MANES MASYARAKAT MARITIM SITUBONDO: ANALISIS SKEMA AKTANSIAL DAN STRUKTUR FUNGSIONAL (Myths of Rokat Aeng Manes Situbondo Maritime Community: Analysis of Actional Schemes and Functional Structures) - NFN Siswanto; NFN Sukatman (Kantor Bahasa Sulawesi Tenggara, 2022)
This research is focused on the folklore of the maritime community in Situbondo, especially the myth of the Rokat aeng manes in Agel Village. Agel's Aeng Manis skirt is an original Situbondo tradition which has its own peculiarities. This traditional ceremony has been going on for generations in the Agel community. The Aeng Manis Rokat Ceremony in Agel Village is a village clean-up ceremony carried out by the Agel community. This ceremony is held to celebrate the harvest and pray for it to be kept away from various logs, diseases, and disasters. This research discusses the myth of the Rokat Aeng Manis ritual in Agel Asembagus, Situbondo village from the perspective of oral tradition with the theory of the Greimas schema and functional structure and the analysis of interpretation in the context of oral history. The method used was ethnography, which emphasizes the active participation of researchers or is directly involved in the community being studied to obtain field notes that can answer research problems. The results describe the phenomenon of violence against women, namely Princess Mayangsari due to the attack of the King of Bali on the Madura Kingdom which is divided into three stages. This condition was resolved with the emergence of the White Tiger (Helper) who was motivated to restore the dignity and glory of the Madura Kingdom.Penelitian ini difokuskan pada folklor masyarakat maritim di Situbondo, khususnya mitos rokat aeng manes di Desa Agel. Rokat Aeng Manis Agel adalah tradisi asli Situbondo yang mempunyai kekhasan tersendiri. Upacara adat ini telah berlangsung turun temurun di masyarakat Agel. Upacara Rokat Aeng Manis di desa Agel merupakan sebuah upacara bersih desa yang dilaksanakan oleh masyarakat Agel. Upacara ini dilaksanakan untuk mensyukuri hasil panen dan mendoakan agar dijauhkan dari berbagai bala, penyakit, dan bencana. Penelitian ini mendiskusikan mitos ritual Rokat Aeng Manis di Desa Agel Asembagus Situbondo dari perspektif tradisi lisan dengan teori skema aktan dan struktur fungsional Greimas dan analisis tafsir dalam konteks sejarah lisan. Metode yang digunakan adalah etnografi yang mengedepankan partisipasi aktif peneliti atau terlibat langsung ke masyarakat yang diteliti untuk mendapatkan catatan lapangan yang dapat menjawab permasalahan penelitian. Hasil penelitian mendeskripsikan fenomena kekerasan terhadap perempuan yakni Putri Mayangsari akibat adanya penyerangan Raja Bali pada Kerajaan Madura yang terbagi menjadi tiga babak. Kondisi tersebut terselesaikan dengan munculnya Macan Putih (helper) yang termotivasi untuk mengembalikan martabat dan kejayaan Kerajaan Madura.